THE LOCAL WISDOM OF THE SUNDANESE-PEOPLE ON CULTURE, LANGUAGE, AND ARABS IN SUMEDANG DISTRICT - Tb. Ace Fahrullah; Ade Kosasih; Yani Rohmayani; Sutiono Mahdi (Universitas Padjadjaran, 2022)
The wisdom of the Sundanese-people of Sumedang towards Arabic culture, language, and arabs is still at the stage of conventional understanding. Understanding has not led to the reality that it should be. This is because the knowledge of the Sundanese-people of Sumedang is relatively and varied in obtaining the transformation of knowledge in the fields of social, political, cultural, linguistic and religious. The transformation of knowledge through education has not been evenly distributed. Education and teaching on geographical, social, and political sciences as well as culture have not been programmed. In the Sundanese-people of Sumedang there has not been a significant change in understanding the fields of Arabic culture, language, and nation. This study aims to describe the understanding of the Sundanese-people of Sumedang towards the Arabic culture, language, and nation, that grow and develop with the times. The method used is descriptive analysis. Data obtained from the literature and interviews. The results show that the understanding of the Sundanese-people of Sumedang towards the Arabic culture, language, and nation is still limited to information provided by non-formal education. Therefore, it is necessary to involve formal education from the Sumedang local government and the private sector.